Nomograms of solid linear viscoelastic materials in time and frequency domains - de Sousa, Tiago Lima; da Silva, Jéderson; Pereira, Jucélio Tomás; Pires, Carolina Mocelin Gomes (Comptes Rendus. Mécanique)
The mechanical behavior of isotropic solid viscoelastic material (VEM) can be described both in time or frequency domain considering temperature effects. Thus, one can make use of viscoelastic functions such as Young’s and/or shear moduli and the Poisson’s ratio. The viscoelastic dynamic behaviors in different temperature and frequency or time ranges can be grouped into a single graph, named nomogram. The present work proposes a method for constructing nomograms for viscoelastic functions, Young’s and shear relaxation moduli, and Poisson’s ratio, defined in the time domain. It also proposed a nomogram for the complex Poisson’s ratio in the frequency domain.